Fuzzy Decision Systems for Sustainable Public Transport: A Literature Review - Kilic, Mehmet; Demirel, Tufan (SPRINGERNATURE, 2025)
The concept of sustainable transport has been proposed and implemented in cities around the world to facilitate transition to sustainability. Reducing carbon emissions and increasing accessibility in an economically feasible way has been the core objective of sustainable transport initiatives in cities. The complexity of the transport systems requires a decision framework that would take this complexity as well as uncertainty into account while proposing solutions for sustainable transport issues. Current worldwide developments, such as the COVID-19 outbreak and international tensions, economic crises, and climate change, have heightened uncertainty regarding decisions that affect sustainable transportation challenges. Classical decision methods are no longer sufficient to tackle sustainable transport issues in this economically, socially, and environmentally uncertain environment. This is evidenced by the rapid proliferation of the studies using some sort of fuzzy decision systems on developing solutions for sustainable transport problems. Fuzzy decision systems provide new frameworks of decision-making that would appropriately take the uncertainty into account for the sustainable transport decisions and problems. This study provides an overview of existing research on studies that utilize fuzzy decision systems for sustainable public transport, excluding logistics transport from its scope. Additionally, a thematic analysis is conducted on the types of fuzzy decision methods and sustainable transport topics, aiming to summarize the existing literature and guide future research in this field.
Keywords: Fuzzy decision systems; Public transport; Sustainable transport; Urban mobility; HYBRID APPROACH; MOBILITY; METHODOLOGY; VEHICLES; TOPSIS; FRAMEWORK; SELECTION; DYNAMICS; IMPACTS; WASPAS; Computer Science